2019
DOI: 10.1186/s12913-019-4194-y
|View full text |Cite
|
Sign up to set email alerts
|

Canonical correlations between individual self-efficacy/organizational bottom-up approach and perceived barriers to reporting medication errors: a multicenter study

Abstract: Background Individual and organizational factors correlate with perceived barriers to error reporting. Understanding medication administration errors (MAEs) reduces confusion about error definitions, raises perceptions of MAEs, and allows healthcare providers to report perceived and identified errors more frequently. Therefore, an emphasis must be placed on medication competence, including medication administration knowledge and decision-making. It can be helpful to utilize an organizational appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
1
6
1
2
Order By: Relevance
“…Error reporting is a key factor in determining effective risk handling. The findings, too, are consistent with those of previous studies: self-efficacy and psychological safety are important attitudinal precursors of prohibitive voice behavior such as error reporting (Emby et al , 2018; Kim and Kim, 2019). Ultimately, this study suggests that establishing an error-tolerant work environment can yield benefits in areas such as job attitudes, learning, voice behavior and job performance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Error reporting is a key factor in determining effective risk handling. The findings, too, are consistent with those of previous studies: self-efficacy and psychological safety are important attitudinal precursors of prohibitive voice behavior such as error reporting (Emby et al , 2018; Kim and Kim, 2019). Ultimately, this study suggests that establishing an error-tolerant work environment can yield benefits in areas such as job attitudes, learning, voice behavior and job performance.…”
Section: Discussionsupporting
confidence: 91%
“…Although previous studies have suggested that self-efficacy might be an important attitudinal driver of error reporting behavior, very few studies have empirically tested this relationship (Zhao and Olivera, 2006). Kim and Kim (2019) revealed the influence of medication administration knowledge and nursing decision-making on perceived barriers to medication administration errors. The current study responded to this call by revealing a positive impact of employees’ self-efficacy on error reporting.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of correct answers varied from 65% to 96%, as shown in Table 4. The mean knowledge of HAMs score obtained in this study (73.2 + 16.4) was higher than in a pilot study conducted in São Paulo (63.6%), 9 in Korea (65%) 19 and in Pakistan (60%). 14 However, the mean presented in the São Paulo study refers to nurses and pharmacy students.…”
Section: Discussioncontrasting
confidence: 84%
“…But additionally, providers reported fear of losing one's job, fear of patient's or family's response to the Not only is "fear of consequences" the most reported factor for underreporting, it also happens to be the most significant factor for underreporting in most of the included studies [14-16, 20-22, 25, 32, 37-40, 42]. While fear of consequences might be more prominent in certain cultures than others and more prominent in hospitals with hierarchical structures [16], it has been reported at both local and international levels and in different management styles. Additionally, fear as a factor has not changed over the years.…”
Section: Fear Of Consequencesmentioning
confidence: 99%